Benefits and challenges of small modular fast reactors : proceedings of a technical meeting. (IAEA-TECDOC ;, 2021)
"In the world market of power-producing nuclear reactors, there is growing interest in small and medium sized or modular reactors (SMRs). These can be assembled in-factory, transported by ship or train, installed on site and connected to the electricity grid in a short time, significantly reducing the financial burden of the investment. This publication, which is the outcome of a technical meeting, presents a detailed overview of the different concepts of fast SMRs and highlights the technological, economic and safety potential of these reactors and the associated innovative systems. Although it is mainly focused on innovative reactor solutions aimed to increase safety and simplicity of design, the parameters that contribute to the final cost of the plant are also considered."--Publisher's description.